Performance, Hematology and Serum Biochemistry of West African Dwarf Goats Fed Ensiled Mixtures of Elephant Grass (Pennisetum purpureum) with Lima Bean, African Yam Bean and Pigeon Pea - Tope, Ajayi Festus; Funmi, Ogunleke; Adewumi, Adesina; Sunday, Durotoye Emmanuel (Agriculture and Natural Resources, 2012)
The performance, hematological and biochemical parameters of 16 West African dwarf goats fed ensiled elephant grass (Pennisetum purpureum) with pineapple pulp (Diet 1), pigeon pea plant (Diet 2), lima bean plant (Diet 3) and African yam bean plant (Diet 4) were investigated in a completely randomized design. Four goats were allotted to each diet in a 91-day feeding trial; each goat was fed at 5% of its body weight. The results showed that the crude protein, ether extract and ash contents of Diets 2–4 were similar (P > 0.05). The dry matter intake, crude protein intake and neutral detergent ﬁ ber intake of goats fed Diet 3 differed signiﬁ cantly (P < 0.05) from that of goats fed Diets 1, 2 and 4 which were 71.2, 28.8 and 52.7 g per kilogram W0.75 per day (metabolic weight per day), respectively. The highest packed cell volume was observed in goats on Diet 2 (29.3%) and differed signiﬁ cantly (P < 0.05) from that of goats fed Diets 1, 3 and 4. Goats fed Diet 3 had the highest hemoglobin concentration, lymphocyte, monocytes and eosinophils. Goats fed Diet 4 had the highest total protein (70.2 g.L-1) and cholesterol (42.0 mmol.L-1).The highest urea nitrogen (3.8 mmol.L-1), creatinine 97.0 μmol.L-1), AST (51.9 IU.L-1), ALT (6.7 IU.L-1), glucose (3.1 mmol.L-1) and lowest cholesterol (31.2 mmol.L-1) were observed in goats fed with Diet 3. These results indicated that ensiling elephant grass with any of these legumes known to contain high concentrations of anti-nutrients was not detrimental to the health of the goats. Diet 3, comprising ensiled elephant grass with lima bean and pineapple pulp, produced the optimal growth rate and weight gain in the goats.